The importance of client compliance and the influences upon client compliance when orally medicating cats. Issue 5 (4th May 2018) - Chapman, Emily
Abstract: Client compliance when delivering oral medication forms a large part of the success or failure of such treatment regimes. The prevalence of antimicrobial resistance (AMR) today may imply that an improvement in antimicrobial stewardship or client compliance needs to be sought. Anecdotal evidence describes cats being difficult to deliver oral medications to, but there are many other factors that may influence a client's ability or willingness to comply. It is important to understand clients' abilities and to help improve their knowledge and skills when orally medicating cats to strive towards the safest and most successful clinical outcome.